POETIC STRUCTURES IN A STORY “BORSA KELMAS DARVOZASI” BY SAID AKHMAD - Gafurova, Gulruh (Журнал иностранных языков и лингвистики, 2021)
This article is about poetic structures in a story “Borsa kelmas darvozasi” by Said Akhmad.